Evidence-based ranking of green building design factors according to leading energy modelling tools. (May 2019) - Alwisy, Aladdin; BuHamdan, Samer; Gül, Mustafa
Highlights: A methodology is presented for identifying and ranking green building design factors. A quantitative survey of green building literature is conducted for the ranking system. Potential benefits to design teams and green building rating systems are proposed. HVAC systems have less influential impact than building envelope elements. Abstract: Green building has been acknowledged as a leading practice for mitigating the environmental impact throughout the life cycle of buildings. Recent studies have explored a wide range of systems, modeling tools, standards, and rating tools to facilitate the implementation of green building design concepts. However, these studies continue to utilize generic design parameters (factors) without considering their impact on the overall building environmental performance. This can lead to delays during the design process as a result of practitioners relying on their intuition to select and prioritize relevant factors. The proposed research establishes an evidence-based ranking system for green building design factors (GBDFs) in order to improve the green building design process based on an extensive systematic literature review. The identification phase of GBDFs is conducted through an extensive review of the literature on green buildings in reference to representative modeling tools. The evaluation phase is then carried out based on the frequency of relevant publications in accordance with leading modeling tools to generate the proposed evidence-based GBDF ranking. This ranking pioneers an innovative endeavor to prioritize GBDFs that not only assists designers, but also establishes baselines for further development of existing modeling tools.